Farm (London Dorling Kindersley Ltd, 2012)
Teach your child all about farms with touch and feel textures in this chunky board book. Twinkly, bumpy, scaly, silky, sandy, sticky and shiny textures in a chunky package will help your child discover all about farms. Oink oink! Quack quack! Let their little hands roam and feel how velvety the pigs nose is and how fluffy the chicks feel
Scientific Notions
1 3 9
Keywords: Science